Altered Effective Connectivity of Bilateral Hippocampus in Type 2 Diabetes Mellitus - Liu, Taiyuan; Bai, Yan; Ma, Lun; Ma, Xiaoyue; Wei, Wei; Zhang, Junran; Roberts, Neil; Wang, Meiyun (Frontiers in Neuroscience, 2020)
Patients with type 2 diabetes mellitus (T2DM) experience cognitive deficits but the underlying pathophysiologic mechanisms are not known. We therefore applied Granger Causality Analysis (GCA) of resting-state functional Magnetic Resonance Imaging (rs-fMRI) to study the Effective Connectivity (EC) of the hippocampus in patients with T2DM. Eighty six patients with T2DM and 84 matched Healthy Controls (HC) were recruited. The directional EC between anatomically defined seeds in left hippocampus (LHIP) and right hippocampus (RHIP) and other brain regions was compared between T2DM and HC and Pearson correlation analysis was performed to determine whether alterations in EC were related to clinical characteristics of diabetes. Compared with HC, patients with T2DM had altered EC between LHIP and RHIP and the Default Mode Network (DMN), occipital cortex and cerebellum. In addition, for LHIP only duration of diabetes positively correlated with decreased inflow from right postcentral gyrus and right parietal lobe, glycosylated hemoglobin (HbA1c) negatively correlated with decreased inflow from right thalamus (r = -0.255, p = 0.018) and MoCA negatively correlated with decreased inflow from left inferior parietal lobe (r = -0.206, p = 0.05). The altered EC between hippocampus and DMN is interpreted to be related to cognitive deficits in patients with T2DM particularly affecting memory and learning.